(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Reading skills are important aspects for foreign language learners who are different types of different ages. The youngsters learn other sections of language: Writing, Speaking, Listening, and gaining information about global topics, followed by positive reading habits through relevant activities. In this article, it is disputed that how to obtain this skill without a long time with being the best reader within society, academic areas, and improved training are related to reading.